P149 Once-daily tiotropium Respimat® add-on to at least ICS in adult patients with symptomatic asthma: pooled safety analysis. (12th November 2015) - Dusser, D; Buhl, R; Castro, M; Kerstjens, HAM; Paggiaro, P; Engel, M; Moroni-Zentgraf, P; Unseld, A; Bateman, ED
Abstract : Background: A high proportion of patients with asthma are symptomatic despite at least ICS maintenance therapy. Five trials aimed to evaluate the safety of tiotropium Respimat® compared with placebo Respimat®, each as add-on to at least ICS in adult patients with symptomatic asthma. Methods: Five Phase III and one Phase II randomised, double-blind, placebo-controlled, parallel-group trials. PrimoTinA-asthma® (48 weeks): tiotropium Respimat® 5 µg add-on to ICS + LABA (≥800 µg budesonide or equivalent); MezzoTinA-asthma® (24 weeks): tiotropium Respimat® 5 µg or 2.5 µg add-on to ICS (400–800 µg budesonide or equivalent); GraziaTinA-asthma® (12 weeks): tiotropium Respimat® 5 µg or 2.5 µg add-on to ICS (200–400 µg budesonide or equivalent); Study 342 (16 weeks): tiotropium Respimat® 5 µg add-on to ICS (400–800 µg budesonide or equivalent). Pooled safety data are presented. Results: 1929 patients received tiotropium Respimat® (PrimoTinA-asthma®, n = 456; MezzoTinA-asthma®, n = 1036; GraziaTinA-asthma®, n = 309; Study 342, n = 128). Frequency of AEs in >2% of patients was comparable in the tiotropium Respimat® 5 µg, tiotropium Respimat® 2.5 µg and placebo Respimat® groups (Table 1 ). No deaths occurred. 110 (5.7%) and 55 (4.4%) patients receiving tiotropium Respimat® and placebo Respimat®, respectively, reported drug-related AEs (cardiac AEs were rare: tiotropium Respimat®, 7 [0.4%]; placebo Respimat®, 3 [0.2%]). One drug-related serious AE (asthma) was reported with tiotropium Respimat®. Conclusion: Once-daily tiotropium Respimat® add-on to at least ICS maintenance therapy in adult patients demonstrates a safety profile comparable with that of placebo and is well tolerated across severities of symptomatic asthma.